Comparison of Two Information Sources for Cause-of-Death Follow-up in the Russian Federation: The Asbest Chrysotile Cohort Study - Schüz, J.; Kovalevskiy, E.; Moissonnier, M.; Olsson, A.; Hashim, D.; Kromhout, H.; Kashanskiy, S.; Chernov, O.; Bukhtiyarov, I.; Ostroumova, E. (Methods of Information in Medicine, 2020)
Background The Asbest chrysotile cohort was set up in Asbest town, Sverdlovsk oblast, Russian Federation, among the current and former workforce of the world's largest operating chrysotile mine and its processing mills, to investigate cancer risk in relation to occupational exposure to chrysotile.Objectives The cohort of 35,837 people was followed-up for mortality using cause-of-death information from official death certificates issued by the Civil Act Registration Office (ZAGS) of Sverdlovsk oblast from 1976 to 2015. Data were also retrieved from the electronic cause-of-death registry of the Medical Information Analytical Centre (MIAC) of Sverdlovsk oblast, which was launched in 1990 and operates independently of ZAGS. The objectives were to compare the completeness of record linkage (RL) with ZAGS and with MIAC, and to compare the agreement of cause-of-death information obtained from ZAGS and from MIAC, with a focus on malignant neoplasms.Methods RL completeness of identifying cohort members in ZAGS and in MIAC was compared for the period 1990 to 2015. In the next step, for the comparison of the retrieved cause-of-death information, 5,463 deaths (1,009 from cancer) were used that were registered in 2002 to 2015, when causes of death were coded using International Statistical Classification of Diseases and Related Health Problems, 10th revision (ICD-10) nomenclature by MIAC. For ZAGS, original cause-of-death text from the death certificates was obtained and then coded according to ICD-10 by the International Agency for Research on Cancer/World Health Organization (IARC/WHO). Agreement was evaluated at various levels of detail, and reasons for any disagreements between the MIAC and the IARC/WHO ICD-10-coded cancer diagnosis were systematically explored.Results A total of 10,886 deaths were obtained from all avenues of follow-up for the period 1990 to 2015 in the cohort; 10,816 (99.4%) of these were found in ZAGS. This percentage was 88.3% if only automated deterministic RL was used and 99.4% when deterministic RL was complemented with manual searches of cohort members. Comparison of the cause-of-death information showed agreement of 97.9% at the ICD-10 main group level between ZAGS (coded by IARC/WHO) and MIAC. Of 1,009 cancer deaths, 679 (67.3%) cases had identical coding, 258 (25.6%) cases corresponded at the three-character ICD-10 level, 36 (3.6%) had codes that were within the same anatomical or morphological cluster, and for only 36 (3.6%) cases were major discrepancies identified. Altogether, the agreement between IARC/WHO coding of cause-of-death information from ZAGS and MIAC coding of malignant neoplasms was therefore 96.4%.Conclusions RL completeness and agreement of cause-of-death information obtained from ZAGS and from MIAC were both very high. This is reassuring for the quality of cancer mortality follow-up of the Asbest chrysotile cohort. For future epidemiological studies in the Russian Federation, ZAGS appears to be a reliable information source for mortality follow-up, if the automated RL is complemented with manual searches of cohort members. MIAC is a good resource for prospective studies.
Keywords: mortality register; cause of death; International Statistical Classification of Diseases and Related Health Problems; asbestos; Russian federation